Entre a tenda e a praça: espaço, territorialidade e identidade circense na capital paranaense - Magalhães, Eloi Vieira (2024)
In Curitiba-Paraná, a peculiar situation arose: the state capital welcomed a circus characterized by family tradition and itinerancy. Over time, the itinerancy ceased and the circus integrated into the city that welcomed it. This resulted in the creation of a public cultural facility, the City Circus Zé Priguiça, focused on circus activities and also functioning as a circus school. This dissertation explores the relationship between the circus and the territory, focusing on the trajectory of the Queirolo Brothers and the City Circus Zé Priguiça in the capital of Paraná. The research analyzes the transition from the itinerant circus to the fixed tent, exploring the social and professional transformations that occurred during this process. The Queirolo Brothers, a traditional circus family and important in the national circus scene, left the itinerancy to establish residence in Curitiba, creating a unique territorial relationship in the context of the circus. The objective is to observe the transformations of the circus over time, due to the adaptations that needed to be made to meet different realities and territories. For this, the study explores the Queirolo Brothers Circus, describing how the group rebuilt its internal and external organization in response to social and professional transformations resulting in the end of itinerancy and the creation of the cultural equipment: City Circus Zé Priguiça. The approach adopted for the research is qualitative and interdisciplinary, using methods such as bibliographic review, documentary and case study. Several authors contributed to the approach of the theme: Saquet, Haesbaert, Ávila (territory); Follmann and Castells (identity); Sacchi, Pimenta, Silva, Lopes and Castro (circus), among others. The research reveals that the circus has undergone significant changes since its origins in the Modern Age to contemporaneity. The transition from the itinerant circus to other urban formats brought a series of social and professional transformations. This includes adapting to new audiences and urban contexts, the need to form local partnerships and seek institutional support, and the introduction of new practices, such as circus schools and social circus projects. These changes contributed to the formation of a multifaceted circus identity, which reflects both the rich tradition of the itinerant circus and the innovations and challenges of the urban circus. The relationships established between the Queirolo Brothers Circus and the capital of Paraná paved the way for a new perspective on the circus in Curitiba, resulting in one of the first and possibly most significant circus policies of the capital of Paraná: the City Circus Zé Priguiça. The study also addresses the impact of circus schools and social circus projects on urban life and circus culture. The dissertation closes by emphasizing the need for effective public policies to support the circus and its social and cultural function. It also highlights the importance of the struggle of circus artists, with the backing of the entire community, for recognition and for the preservation and celebration of the circus, a heritage of our culture.